Hydrogen production via methane dry reforming process over CoAl and CoMgAl-Hydrotalcite derived catalysts. Issue 1 (October 2021) - Abdelsadek, Z; Chaudhari, P; Holgado, J P; Bali, F; Halliche, D; Cherifi, O; Gonzalez-Cortes, S; Masset, P J
Abstract: Co0.67 Al0.31 and Co0.14 Mg0.54 Al0.31 hydrotalcite based catalysts were prepared by a co-precipitation method at a fixed pH=11, exhibiting a suitable hydrotalcite structure to be used as a catalyst in the reaction of the dry reforming of methane (DRM). Calcination at 450 °C provides the best conditions to prepare the most adapted structure and morphology to be later used in the DRM reaction. The samples were characterised by XRD, FTIR, SEM and it was shown that they exhibit a specific surface in the 30-70 g/cm 2 and a crystallite size of approximately 20 nm. The results of the TPR analysis showed clearly that CoAl-HT has better catalytic performances than CoMgAl-HT. This result can be explained by the presence of the Co 0 for the catalyst CoAl-HTc-R and the total absence in the sample CoMgAl-HTc-R. The solid CoMgAl-HTc-R requires high reduction temperature compared to CoAl-HTc-R due to the strong CoO-MgO interactions.